Rapid progression and short-term mortality during the January 2023 to July 2024 Cholera outbreaks in Zambia: A retrospective facility-based study - Deborah Tembo; Nedah Chikonde Musonda; Miyanda Simwaka; Chipo Nkwemu; Samson Shumba (PLoS ONE, 2025)
Cholera remains one of the most rapidly fatal infectious diseases globally, with untreated cases leading to death within hours due to severe dehydration. Despite being preventable and treatable, it continues to pose a significant public health threat, especially in low and middle-income countries where water, sanitation, and hygiene (WASH) services are inadequate. This study aimed at investigating the rapid progression and short-term mortality during the January 2023 to July 2024 Cholera Outbreaks in Zambia. We conducted a retrospective cross-sectional study using national cholera surveillance data from Zambia’s January 2023 to July 2024 outbreak to examine delays in care and associated outcomes. All suspected and confirmed cases with complete records on symptom onset, admission, and outcome were included. Key time intervals were calculated and analyzed using descriptive statistics and non-parametric tests, with subgroup comparisons by age, sex, and outcome status. Ethical approval was obtained, all data were anonymized, and analyses were performed using Stata version 14.2. A total of 3,655 cases were analyzed, of whom 52.2% were male and 37.8% were under 15 years. Nearly all patients (99%) were admitted as inpatients, and the overall mortality rate was 4.2%. The median time from symptom onset to death was 3 days, underscoring the rapid progression of the disease. Of the 3,655 cholera patients enrolled in the study, 2,162 patients were included in the survival analysis, the death rate was 0.85 per 100 person-days, with higher rates observed among males (1.05) and adults aged 50 years and above (2.71). Confirmed cases experienced the highest mortality, and survival probabilities were significantly lower among males (p = 0.0498), older adults (<0.0001), and confirmed cholera cases (<0.0001). Many cholera deaths in this outbreak happened within just a few days of admission, showing the need for quick assessment and urgent fluid treatment as soon as patients arrive. Older adults and men faced a higher risk of dying, which calls for triage protocols that pay closer attention to these groups. Laboratory confirmation was limited, with very few patients receiving rapid diagnostic tests, revealing a serious gap in surveillance and case management. Strengthening early warning systems, improving access to rapid tests, and focusing on high-risk groups are key steps to lowering deaths in future outbreaks.